Observaciones de campo sobre dinoflagelados raros o desconocidos en el Mar Argentino - Fabro Cerreia Fus, Elena Ines (2021)
Background and aims: Planktonic dinoflagellates have a great ecological significance in marine environments. While some dinoflagellate species commonly reach bloom concentrations and are thus conspicuous components of marine phytoplankton, others occur in very low abundances which make them difficult to detect in field studies. Here we analyzed dinoflagellate composition and abundance in five oceanographic expeditions carried out in continental shelf and slope waters of the Argentine Sea. M&M: Plankton abundance was estimated by the Utermöhl method, using inverted microscopy, whereas further optical and scanning electron microscopy was applied for the identification of dinoflagellate species. Results: We focused on the occurrence of seven dinoflagellates that have been previously poorly documented or overlooked in marine environments worldwide: Dinophysis microstrigiliformis; Gyrodinium sp.; Karlodinium elegans; Oxytoxum laticeps; Peridiniella danica; Peridiniella globosa and Prorocentrum nux. The latest and K. elegans are observed for the first time in field conditions after their original descriptions based on cell cultures. While most species were detected in low or moderate abundances, P. nux, which is the smallest Prorocentrum species, reached 82,000 cells L-1 in slope waters. Very small Gyrodinium cells (11.5 µm long; 8.7 µm wide) with a distribution restricted to slope waters during spring, were not possible to be accurately assigned to a species. Conclusions: This study contributes to the understanding of dinoflagellate diversity in the Argentine Sea and the worldwide distribution of little known species.